Push, Pull, and Mooring Factors in Consumer Switching and Continuance Intention in the Fuel Industry : Faktor Push, Pull, dan Mooring dalam Perpindahan serta Keberlanjutan Konsumen pada Industri BBM - Jatmiko, Lovia Vioni Putri; Waluyo, Minto (Academia Open, 2026)
General Background: Consumer switching behavior is important in essential service markets because purchasing decisions are shaped by dissatisfaction, alternative attractiveness, and switching barriers. Specific Background: In the fuel industry, consumers may move from local to private providers when prior service experiences reduce trust and create perceptions of higher value from alternative providers. Knowledge Gap: Previous Push Pull Mooring studies have been widely applied in e-commerce, digital banking, and technology-based services, while their application in the fuel industry remains limited, particularly in a model linking switching intention, switching behavior, and continuance intention. Aims: This study aimed to analyze push, pull, and mooring factors on switching intention, switching behavior, and continuance intention among fuel consumers. Results: Using a quantitative approach with covariance-based Structural Equation Modeling through AMOS, data from 140 respondents showed that push factors had a positive and significant relationship with switching intention. Pull and mooring factors were not significant. Switching intention significantly related to switching behavior, and switching behavior significantly related to continuance intention. The modified model met goodness-of-fit criteria, with probability of 0.376, CMIN/DF of 1.045, RMSEA of 0.018, GFI of 0.937, TLI of 0.991, and CFI of 0.994. Novelty: This study applies the Push Pull Mooring framework to consumer switching in the fuel industry. Implications: The findings suggest that providers should prioritize reducing dissatisfaction, strengthening service reliability, and maintaining positive post-switching experiences. Highlights: Prior dissatisfaction became the main reason behind consumer movement. Alternative attractiveness and barriers were not statistically significant. Actual movement supported continued private provider usage. Keywords: Continuance Intention, Push-Pull-Mooring, Structural Equation Modeling (SEM), Switching Intention, Switching Behavior